The representation of the family’s voice in serious case review reports of child maltreatment - Laird, Siobhan E. (Taylor & Francis, 2017)
Australia and the United Kingdom have a mandatory system of case reviews, which are conducted whenever a child known to welfare or health services has died or been seriously harmed due to maltreatment. In the United Kingdom those conducting case reviews are required to involve family members in their deliberations. This study employed discourse analysis to examine the representation of family voices in 41 Overview Reports of Serious Case Reviews undertaken in England and published during 2014. The findings revealed that the contributions of family members were generally relegated or their legitimacy undercut by the positivist framing of most Overview Reports. However, the research also identified how the framing of family contributions within an interpretivist paradigm could engender highly complex understanding of deficiencies in child protection systems and lead to crucial new learning for professionals.